Educational Service Approach for Children with Special Needs - Thiara Deah Lestari (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
This research aims to explore effective educational service approaches for children with special needs through the Systematic Literature Review (SLR) method. This method is used to identify, evaluate, and interpret all relevant research on the studied topic. The focus of the research includes three main elements: inclusive approaches, the use of educational technology, and collaboration between parents, teachers, and other professionals. The results of the literature review indicate that an inclusive approach allows children with special needs (CSN) to learn in a supportive environment, which can enhance their social engagement and academic achievement. The use of educational technology, such as specialized software and communication aids, has proven effective in overcoming learning barriers and improving children's cognitive and motor skills. Moreover, close collaboration between parents, teachers, and other professionals is crucial in designing and implementing a comprehensive and consistent Individualized Education Plan (IEP). This research concludes that an integrated and inclusive educational service approach can provide children with special needs the best opportunities to reach their full potential in a supportive and adaptive environment.